(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The rapid integration of Artificial Intelligence (AI) into education has led to significant advancements in English language learning. This paper examines the potential of AI tools, including adaptive learning platforms, speech recognition software, and immersive technologies, to personalize learning experiences and improve linguistic proficiency. Drawing from recent research and case studies, it discusses benefits, such as scalability and engagement, alongside challenges like ethical concerns and technological dependency. The study concludes that a hybrid approach, blending AI with human instruction, offers the most effective way forward.